Self-tuning adaptive multi-rate control for energy efficient wireless networked control systems - Mansano, Raul K. [UNESP]; Rodrigues, Renan J. [UNESP]; Godoy, Eduardo P. [UNESP]; Colon, Diego (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Recent advances in wireless technologies and the proliferation of wireless sensors led to an increasing interest in Wireless Networked Control Systems (WNCS). A major issue in WNCS is the battery lifetime of the wireless sensors, which are a limited source of power. As the wireless transmission requires high-energy expenditure, it is imperative to reduce the number of wireless transmissions in order to save battery. This paper develops a multi-rate adaptive controller for energy efficient application of WNCS. A self-tuning adaptive controller is applied to identify the WNCS model, simulate that model and tune the controller parameters at each control step, providing robustness to disturbance and inherent nonlinearities of the WNCS. The novelty is the addition of a multi-rate control technique, so the resulting controller can process data from the simulated model to compute additional control signals, allowing the reduction of sensor sampling frequency. By reducing frequency of wireless transmissions, it is possible to reduce power expenditure of the wireless devices. Experimental results show that this strategy is effective and allow power saving for wireless sensors batteries without compromising the control performance.